The Factors Influence the Improvement of Students’ Reading Comprehension in Narrative Text through SQ3R Reading Methods of The Third-Year Students at SMPN 2 Kampar Kiri - Andhini, Aulia; Tasyakurna M, Annisa; Widi, Rahma (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study discussed the factors that influence the improvement of students’ reading comprehension in narrative text. By using SQ3R, it is an effective method to teach students reading comprehension. The method used in this research was descriptive research as the research design. The participants in the research study consisted of third-year students at SMPN 2 Kampar Kiri of Class 9.2. The results of this research are: first, the student’s interest in using the SQ3R reading method found from interviews the research which showed that they were interested and enjoyed learning reading using the SQ3R reading method. Second, the students’ motivation in reading. It was also found from the interviews done during the research that they had more motivation to be involved in the reading class. Third, the use of the SQ3R reading method had given more advantages in learning reading text; they could comprehend the text easily and answer the question quickly. Thus, this method is effective to use in comprehending reading the narrative text. It can improve students’ ability in understanding the text. Therefore, the SQ3E method is suitable to be implemented in teaching reading comprehension.